OTC intron 4 variations mediate pathogenic splicing patterns caused by the c.386G>A mutation in humans and spfash mice, and govern susceptibility to RNA-based therapies - Claudia Sacchetto; Laura Peretto; Francisco Baralle; Iva Maestri; Francesca Tassi; Francesco Bernardi; Stan F. J. van de Graaf; Franco Pagani; Mirko Pinotti; Dario Balestra (BMC, 2021)
Abstract Background Aberrant splicing is a common outcome in the presence of exonic or intronic variants that might hamper the intricate network of interactions defining an exon in a specific gene context. Therefore, the evaluation of the functional, and potentially pathological, role of nucleotide changes remains one of the major challenges in the modern genomic era. This aspect has also to be taken into account during the pre-clinical evaluation of innovative therapeutic approaches in animal models of human diseases. This is of particular relevance when developing therapeutics acting on splicing, an intriguing and expanding research area for several disorders. Here, we addressed species-specific splicing mechanisms triggered by the OTC c.386G>A mutation, relatively frequent in humans, leading to Ornithine TransCarbamylase Deficiency (OTCD) in patients and spfash mice, and its differential susceptibility to RNA therapeutics based on engineered U1snRNA. Methods Creation and co-expression of engineered U1snRNAs with human and mouse minigenes, either wild-type or harbouring different nucleotide changes, in human (HepG2) and mouse (Hepa1-6) hepatoma cells followed by analysis of splicing pattern. RNA pulldown studies to evaluate binding of specific splicing factors. Results Comparative nucleotide analysis suggested a role for the intronic +10-11 nucleotides, and pull-down assays showed that they confer preferential binding to the TIA1 splicing factor in the mouse context, where TIA1 overexpression further increases correct splicing. Consistently, the splicing profile of the human minigene with mouse +10-11 nucleotides overlapped that of mouse minigene, and restored responsiveness to TIA1 overexpression and to compensatory U1snRNA. Swapping the human +10-11 nucleotides into the mouse context had opposite effects. Moreover, the interplay between the authentic and the adjacent cryptic 5'ss in the human OTC dictates pathogenic mechanisms of several OTCD-causing 5'ss mutations, and only the c.386+5G>A change, abrogating the cryptic 5'ss, was rescuable by engineered U1snRNA. Conclusions Subtle intronic variations explain species-specific OTC splicing patterns driven by the c.386G>A mutation, and the responsiveness to engineered U1snRNAs, which suggests careful elucidation of molecular mechanisms before proposing translation of tailored therapeutics from animal models to humans.